Porto as a literary touristic destination based on Camilo Castelo Branco’s literary work - Ferreira, Ana (2020)
In this article we intend to show the importance of the work of Camilo Castelo Branco in the promotion of literary tourism in Porto. Literary tourism, being focused on the lifestyle and identity of local communities, local tourism will be a tourism that proposes activities based on local identity and memory and takes into account the preservation of available resources. Therefore, we may ask: What is the role of literature in the valuation of tourism? Can literary tourism define the course of tourism in a specific territory? What is the role of the literary work of Camilo Castelo Branco in the Porto city tourism? Firstly, we intend to clarify the importance of this interdisciplinary research—literary tourism and Camilo Castelo Branco’s work. Next, we would like to focus that a wider value of competitive bids is a valuable asset for tourism development, since the tourist value of a destination depends largely on its ability to affirm itself as a national and international brand. The methodology to follow will be based on the analysis of the available bibliography leading to the consolidation of the idea that Camilo Castelo Branco is an author of the nineteenth century, whose work remains current and may constitute an indispensable tool for the promotion of literary tourism in Porto.